Gerakan Pencegahan Stunting Pada Balita Bersama Mahasiswa Kukerta Universitas Riau Di Desa Kota Baru, Kecamatan Tapung Hilir, Kabupaten Kampar - Marnelia Marnelia; Winda Br Simatupang; Tedi Ramadani; Tiara Zulva; Dinda Aulia Rahmi; Pianti Azirah; Romadhani Romadhani; Jannatul Ma’wa; Masythah Aini; Muhammad Zaki; Rizky Febriansyah Siregar (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Stunting is a condition where a child's height is lower than the height according to his age, which is caused by long-term malnutrition in the first 1,000 days of life (HPK). Apart from nutritional factors, stunting is also caused by a lack of understanding among the public, especially mothers with young children, regarding the problem of stunting. The aim of this community empowerment is to prevent stunting through community participation in monthly village activities by holding posyandu for toddlers and children of pregnant women in Kota Baru village. The method of implementing the activity is community participation in posyandu activities providing vitamin A. The conclusion of this research is that the stunting prevention movement through posyandu activities by providing vitamin A to children under five and providing complementary breast milk food to pregnant women can improve the community. awareness of the importance of nutritious food for children to prevent stunting. Regarding government programs related to stunting, Kukerta University students in Riau are collaborating with the Kota Baru Village Government to continue government programs by implementing monthly programs in the form of posyandu operations as a form of the government's efforts to prevent stunting. . The results of the implementation of posyandu activities carried out by Kukerta Riau University students were two activities, posyandu for toddlers and posyandu for pregnant women. Activities carried out include providing additional food for pregnant women and vitamin A supplements for toddlers.